(untitled) (Fiep Bulletin - online, 2014)
The anxiety is one of the emotional upset more common of the present time. The applied treatments to the anxiety are traditional, expensive and slow. Being like this, this study search to corroborate with other works, in the sense of, to find in the physical activity an alternative for the prevention and treatment of the anxious upset comparing the levels of anxiety line-state among Professionals of Education with participation or not in programs of controlled physical activity and regulated. For that a research work was accomplished, using, in four different groups, the Questionnaire of evaluation of the Anxiety (IDATE), where it was verified that, the practicing group of physical activity to regulate it presented indicative scores of anxiety line-state smaller than the other groups that didn’t practice physical activity to regulate and mainly with relationship to the group that never practiced physical activity to regulate. We can point out that was possible to observe that, the practicing individuals of regular physical exercises, although without the control of the frequency, duration, volume and intensity previously established, they presented lower values for scores of anxiety line-state.